The Swedish National Forest Inventory - Mathur, K. B. L.; Tewari, D. N. (Indian Forester, 1968)
At the instance of the Government, forest inventories have been carried out since 1923. With the data obtained, it is possible to study the changes in the country’s forest wealth. The inventory gives a land classification including a detailed description of the forest area, size and composition of growing stock, the rate of growth, regeneration conditions, soil types under various covers and total annaul cut of the country. Special problems of biological, geological and technical in nature can also be studied on the basis of data collected throughout the country within a year.